2014
DOI: 10.1016/j.anr.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Aggression in South Korean Middle School Students

Abstract: Findings indicate that depression, academic stress, and grade (second grade) influence aggression. To decrease aggressive behavior, it is necessary to provide systematic and political programs in schools and local communities that can ameliorate negative emotional factors like depression and academic stress. Additionally, development of positive factors such as self esteem, decision-making skills, and happiness in middle school students is important to reduce aggression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Some studies supported the notion of a negative impact of aggression on physical, mental and social consequences (Cook, Williams, Guerra, Kim & Sadek, 2010;Espelage, Low, Polanin, & Brown, 2013;Wang et al, 2013). In a descriptive study, Park et al (2014) showed a negative impact of aggression on social consequences. He stated that aggression in adolescence causes hinders healthy interpersonal relationships and juvenile crimes, and can develop into social maladjustment and criminal behavior in adulthood.…”
Section: Earlier Studiesmentioning
confidence: 83%
See 2 more Smart Citations
“…Some studies supported the notion of a negative impact of aggression on physical, mental and social consequences (Cook, Williams, Guerra, Kim & Sadek, 2010;Espelage, Low, Polanin, & Brown, 2013;Wang et al, 2013). In a descriptive study, Park et al (2014) showed a negative impact of aggression on social consequences. He stated that aggression in adolescence causes hinders healthy interpersonal relationships and juvenile crimes, and can develop into social maladjustment and criminal behavior in adulthood.…”
Section: Earlier Studiesmentioning
confidence: 83%
“…Many studies have discussed theoretical models for aggression, which describe the relationship between aggressive factors (e.g., depression, low self-esteem or family conflicts), expressed aggression (as the behavioral reaction to potential aggressive factors with indicators such as violence and anger) and aggression outcomes (e.g., criminal behavior or academic failure) (Nissimov-Nahum, 2009;Coie and Dodge, 1998;Findling, 2003). Studies have shown that the occurrence of aggressive factors is related to expressed aggression (Haapasalo & Tremblay, 1994;Park, Choi & Lim, 2014) as well as aggression outcomes among students (Wang et al, 2013;Park, Choi & Lim, 2014;Kim & Lee, 2008). Furthermore, expressed aggression is related to negative aggression outcomes, and high levels of expressed aggression seem to be a serious issue for many students (Kim & Lee, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCT has also informed studies on aggression among South Korean youth (Kim & Kim, 2008). Korean Children and Youth Services Review 55 (2015) 1-9 literature shows that parental monitoring (Han & Grogan-Kaylor, 2012;Kim & Kim, 2008;Lee, Onifade, Teasley, & Noel, 2012) and positive self-esteem (Hong & Kim, 2011;Park, Choi, & Lim, 2014) are likely to reduce aggressive behavior among South Korean youth, while substance use is related to increased aggressive behavior.…”
Section: Introductionmentioning
confidence: 97%
“…South Korean youths are under a lot of pressure to perform well in school and university (Chandran, 2014;Lee et al, 2010;Park et al, 2014). In South Korea school and university students experience tremendous family and social pressure to perform well in academics.…”
Section: Introductionmentioning
confidence: 99%